2022
DOI: 10.1155/2022/4118976
|View full text |Cite|
|
Sign up to set email alerts
|

Levels of Serum IGF-1, HCY, and Plasma BNP in Patients with Chronic Congestive Heart Failure and Their Relationship with Cardiac Function and Short-Term Prognosis

Abstract: Objective. To investigate the levels of serum insulin like growth factor-1 (IGF-1), homocysteine (HCY), and plasma brain natriuretic peptide (BNP) in patients with chronic congestive heart failure (CCHF) and their relationship with cardiac function and short-term prognosis. Methods. A total of 95 patients with CCHF admitted to our hospital from October 2017 to December 2018 were selected as the observation group. Patients conform to grade II∼IV of the New York Heart Association (NYHA) heart function class. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In fact, we have demonstrated that the CHF group exhibits lower entropy value compared to the control. Moreover, several studies have observed that during CHF, the plasma concentration of BNP increases proportionally to the severity of the cardiac event 56 . Therefore, the higher the BNP value, the more severe the CHF and the lower should be the entropy value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we have demonstrated that the CHF group exhibits lower entropy value compared to the control. Moreover, several studies have observed that during CHF, the plasma concentration of BNP increases proportionally to the severity of the cardiac event 56 . Therefore, the higher the BNP value, the more severe the CHF and the lower should be the entropy value.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have observed that during CHF, the plasma concentration of BNP increases proportionally to the severity of the cardiac event. 56 Therefore, the higher the BNP value, the more severe the CHF and the lower should be the entropy value. A negative correlation was also found between entropy in the theta frequency band and the NYHA scale scores.…”
Section: Channelsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%